PEDIATRIC HODGKIN LYMPHOMA IN LOW- and MIDDLE-INCOME COUNTRIES (LMICs). A NARRATIVE REVIEW - Maria Luisa Moleti; Anna Maria Testi (Mediterranean Journal of Hematology and Infectious Diseases)
Pediatric Hodgkin lymphoma (HL) is a curable disease for more than 90% of children and adolescents in high income countries. However, similar results cannot be achieved, particularly for advanced disease, in low- and middle-income countries (LMICs), where challenging socioeconomic realities and the consequent scarcity of local resources heavily impact on the treatment and patients’ outcome. Information regarding the management and outcome of pediatric HL in LMICs is still limited. In this narrative review, we summarize the results reported in the literature so far and discuss the critical key points that have emerged from this overview.